Nonaqueous dispersion and method for producing laminate

JP2025026200APending Publication Date: 2025-02-21AGC INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023131639
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-10
Publication Date
2025-02-21

AI Technical Summary

Benefits of technology

【0007】 本開示の一実施形態によれば、テトラフルオロエチレン系ポリマーを含む粒子の沈降が抑制され、保存後の粘度維持率に優れる非水系分散液、及びこれを用いる積層体の製造方法が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025026200000001
    Figure 2025026200000001
Patent Text Reader

Abstract

To provide a nonaqueous dispersion that prevents settling of particles containing a tetrafluoroethylene-based polymer, ensuring effective viscosity retention post-storage, and a method for producing a laminate using the same.SOLUTION: A nonaqueous dispersion comprises particles containing a tetrafluoroethylene-based polymer, a nonaqueous dispersion medium, and cellulose with a hydroxyalkyloxy group, with a water content of 10,000 mass ppm or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a non-aqueous dispersion and a method for producing a laminate. [Background technology]

[0002] Fluorine resins are used in various fields because of their excellent physical properties such as electrical characteristics, water and oil repellency, chemical resistance, heat resistance, etc. In particular, tetrafluoroethylene-based polymers are excellent in physical properties such as mold releasability, electrical insulation, water and oil repellency, chemical resistance, weather resistance, heat resistance, etc., and are used by being processed into various molded articles. For example, Patent Document 1 proposes a non-aqueous dispersion of fluororesin particles containing a compound having a terpene skeleton. The non-aqueous dispersion of fluororesin particles described in Patent Document 1 is said to have excellent redispersibility even after long-term storage, and to be able to impart good adhesion without aggregation when added to resin materials such as various thermosetting resins, lubricants, greases, varnishes, paints, etc. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2021-181537 A Summary of the Invention [Problem to be solved by the invention]

[0004] The redispersibility after long-term storage in Patent Document 1 is determined by checking the movement of the dispersion after storage or when the bottle is suddenly tilted by 90 degrees from a stationary state. However, in non-aqueous dispersion, particles containing tetrafluoroethylene-based polymers tend to settle, and it is desired to suppress the settling of particles.When particles containing tetrafluoroethylene-based polymers settle, the liquid properties such as viscosity tend to fluctuate during storage, and it becomes difficult to obtain a molded product of a certain quality from non-aqueous dispersion.Therefore, even if the fluidity of dispersion is confirmed within a certain range, it is desired to suppress the settling of particles containing tetrafluoroethylene-based polymers and to reduce the change in viscosity after storage.

[0005] In view of such circumstances, one embodiment of the present disclosure relates to providing a nonaqueous dispersion in which sedimentation of particles containing a tetrafluoroethylene-based polymer is suppressed and which has an excellent viscosity retention rate after storage, and a method for producing a laminate using the same. [Means for solving the problem]

[0006] The present disclosure includes the following aspects. <1> A non-aqueous dispersion containing particles containing a tetrafluoroethylene-based polymer, a non-aqueous dispersion medium, and cellulose having a hydroxyalkyloxy group, the non-aqueous dispersion having a water content of 10,000 ppm by mass or less. <2> The viscosity at 25°C is 50 mPa·s or more. <1> The non-aqueous dispersion according to claim 1. <3> The tetrafluoroethylene-based polymer contains units based on tetrafluoroethylene and at least one of units based on perfluoro(alkyl vinyl ether) and units based on hexafluoropropylene. <1> or <2> The non-aqueous dispersion according to claim 1. <4> The tetrafluoroethylene-based polymer has a carbonyl group-containing group. <1> ~ <3> The non-aqueous dispersion according to any one of claims 1 to 5. <5> The tetrafluoroethylene-based polymer has 10 to 5,000 carbonyl-containing groups per 1 × 10 carbon atoms in the main chain. <4> The non-aqueous dispersion according to claim 1. <6> The content of the particles containing the tetrafluoroethylene-based polymer is 30 to 70 mass %. <1> ~ <5> The non-aqueous dispersion according to any one of claims 1 to 5. <7> The non-aqueous dispersion medium contains at least one selected from the group consisting of amides, ketones, and esters. <1> ~ <6> The non-aqueous dispersion according to any one of claims 1 to 5. <8> The cellulose has at least a portion of its hydroxyl groups modified with alkyl groups. <1> ~ <7> The non-aqueous dispersion according to any one of claims 1 to 5. <9> In the cellulose, a proportion of a hydroxyalkyl moiety, which is a partial structure of the hydroxyalkyloxy group, is 50 to 80 mass %. <1> ~ <8> The non-aqueous dispersion according to any one of claims 1 to 5. <10> The content of the cellulose relative to the content of the particles containing the tetrafluoroethylene-based polymer is 3% by mass or less. <1> ~ <9> The non-aqueous dispersion according to any one of claims 1 to 5. <11> The content of the cellulose in the total amount of the nonaqueous dispersion is 2% by mass or less. <1> ~ <10> The non-aqueous dispersion according to any one of claims 1 to 5. <12> The moisture content is 1000 mass ppm or less. <1> ~ <11> The non-aqueous dispersion according to any one of claims 1 to 5. <13> The thixotropy ratio calculated by dividing the viscosity η1 measured at a rotation speed of 30 rpm by the viscosity η2 measured at a rotation speed of 60 rpm is 6 or less. <1> ~ <12> The non-aqueous dispersion according to any one of claims 1 to 5. <14> Further comprising a surfactant, <1> ~ <13> The non-aqueous dispersion according to any one of claims 1 to 5. <15> The substrate is <1> ~ <14> 2. A method for producing a laminate, comprising applying the nonaqueous dispersion liquid according to any one of claims 1 to 11, heating to remove the nonaqueous dispersion medium, and further heating to melt and sinter the particles containing the tetrafluoroethylene-based polymer. Effect of the Invention

[0007] According to one embodiment of the present disclosure, there is provided a non-aqueous dispersion in which sedimentation of particles containing a tetrafluoroethylene-based polymer is suppressed and which has an excellent viscosity retention rate after storage, and a method for producing a laminate using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, the form for carrying out the embodiment of the present disclosure will be described in detail. However, the embodiment of the present disclosure is not limited to the following embodiment. In the following embodiment, the components (including element steps, etc.) are not essential unless specifically stated. The same applies to the numerical values ​​and their ranges, and they do not limit the embodiment of the present disclosure.

[0009] In the present disclosure, the term "step" includes not only a step that is independent of other steps, but also a step that cannot be clearly distinguished from other steps as long as the purpose of the step is achieved. In the present disclosure, a numerical range indicated using "~" includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively. In the present disclosure, each component may contain multiple types of the corresponding substance. When multiple types of substances corresponding to each component are present in the non-aqueous dispersion, the content or amount of each component means the total content or amount of the multiple substances present in the non-aqueous dispersion, unless otherwise specified. In the present disclosure, multiple types of particles corresponding to each component may be included. When multiple types of particles corresponding to each component are present in the non-aqueous dispersion, the particle size of each component means the value for a mixture of the multiple types of particles present in the non-aqueous dispersion, unless otherwise specified. In the present disclosure, the terms "layer" and "film" include cases where the layer or film is formed over the entire area when the area in which the layer or film is present is observed, as well as cases where the layer or film is formed over only a portion of the area. In this disclosure, the term "lamination" refers to stacking layers, where two or more layers may be bonded together or two or more layers may be removable. In the present disclosure, a "unit" in a polymer means an atomic group based on a monomer formed by polymerization of the monomer. The unit may be a unit formed directly by a polymerization reaction, or may be a unit in which a part of the unit is converted into a different structure by treating the polymer. Hereinafter, a unit based on monomer a is also simply referred to as a "monomer a unit."

[0010] In this disclosure, the "melting temperature" of a tetrafluoroethylene-based polymer is the temperature corresponding to the maximum value of the melting peak of the polymer measured by differential scanning calorimetry (DSC). In the present disclosure, the "melt flow rate" of a tetrafluoroethylene-based polymer means the melt mass flow rate of the polymer as defined in JIS K 7210-1:2014 (ISO1133-1:2011). In the present disclosure, the "glass transition temperature (Tg)" of a tetrafluoroethylene-based polymer is a value measured by analyzing the polymer by dynamic mechanical analysis (DMA).

[0011] In the present disclosure, the average particle diameter of particles means the volume average particle diameter (D50), which is the volume-based cumulative 50% diameter of particles obtained by a laser diffraction / scattering method. That is, the particle size distribution is measured by a laser diffraction / scattering method, a cumulative curve is obtained with the total volume of the particle group as 100%, and the particle diameter is the point on the cumulative curve where the cumulative volume is 50%. The D50 of a particle is obtained by dispersing the particles in water and analyzing them by a laser diffraction / scattering method using a laser diffraction / scattering type particle size distribution measuring device (for example, a laser diffraction / scattering particle size distribution measuring device "LS-13 320" manufactured by Beckman Coulter, Inc.).

[0012] In the present disclosure, the "specific surface area" is a value calculated by measuring particles by a gas adsorption (constant volume method) BET multipoint method, and is determined using a BET specific surface area measurement device (for example, NOVA4200e (manufactured by Quantachrome Instruments)).

[0013] In the present disclosure, the content of the hydroxyalkyl moiety, which is a partial structure of the hydroxyalkyloxy group, and the average degree of substitution A, the average degree of substitution B, the degree of substitution C, and the degree of substitution D described below are determined by the method described in "Determination of Alkoxyl Substitution Ether by Gas Chromatography" by JG Cobler et al.

[0014] The "water content" of the non-aqueous dispersion in the present disclosure is a value measured by the Karl Fischer method in accordance with JIS K 0068:2001. In the present disclosure, the "viscosity" of a non-aqueous dispersion is determined by measuring the non-aqueous dispersion using a Brookfield viscometer at 25° C. and a rotation speed of 30 rpm. The measurement is repeated three times, and the average value of the three measured values ​​is used. In the present disclosure, the "thixotropy ratio" of a non-aqueous dispersion is a value calculated by dividing the viscosity η1 of the non-aqueous dispersion measured at a rotation speed of 30 rpm by the viscosity η2 measured at a rotation speed of 60 rpm. Each viscosity measurement is repeated three times, and the average value of the three measured values ​​is used.

[0015] <Non-aqueous dispersion> The non-aqueous dispersion of the present disclosure contains particles containing a tetrafluoroethylene-based polymer, a non-aqueous dispersion medium, and cellulose having a hydroxyalkyloxy group, and has a water content of 10,000 ppm by mass or less. Hereinafter, the tetrafluoroethylene polymer is also referred to as "F polymer," and the particle containing the tetrafluoroethylene polymer is also referred to as "F particle." Moreover, the cellulose having a hydroxyalkyloxy group is also referred to as "modified cellulose." In the non-aqueous dispersion having the above-mentioned composition, the sedimentation of the F particles is suppressed and the viscosity retention rate after storage is excellent. The reason for this is not clear, but is presumed to be as follows.

[0016] The present inventors have found through experimental studies that the incorporation of a specific modified cellulose is effective in suppressing the sedimentation of F particles in a non-aqueous dispersion and improving the viscosity retention rate after storage. In such modified cellulose, at least a part of the hydroxyl groups of cellulose is modified with a hydroxyalkyl group. In other words, such modified cellulose is a compound having a structure in which the length from the six-membered ring to the hydroxyl group is extended by an alkyl group and has a hydroxyl group at the end of the alkyl group, in other words, a low polarity moiety and a high polarity moiety are linked via a spacer as a unit. It is presumed that the uneven distribution of polarity of such modified cellulose balances the affinity with the solvent and the F particles, and exerts the thickening effect of the dispersion. On the other hand, it has been found that modified cellulose can be affected by the external environment, and in particular, it can be hydrolyzed by moisture, resulting in the elimination of the modified hydroxyalkyl group. Therefore, by setting the moisture content of the non-aqueous dispersion to 10,000 ppm by mass or less, it is believed that the effect of the external environment on the modified cellulose can be suppressed and the viscosity retention rate of the non-aqueous dispersion medium can be improved. Each component contained in the non-aqueous dispersion will be described below.

[0017] (F particle) The F polymer contained in the F particles is a polymer containing units (hereinafter also referred to as "TFE units") based on tetrafluoroethylene (hereinafter also referred to as "TFE units"). From the viewpoint of favorably expressing the characteristics due to the TFE units, the content of the TFE units in the F polymer is preferably 50 mol% or more, more preferably 90 mol% or more, based on the total units in the F polymer. The content may be 99 mol% or less, or 98 mol% or less.

[0018] The F polymer may be either heat-fusible or non-heat-fusible. When it is desired to exhibit particularly good properties such as thermal conductivity, adhesiveness, and processability, the F polymer is preferably heat-fusible. A heat-fusible polymer means a polymer that has a temperature at which the melt flow rate is 1 to 1000 g / 10 min under a load of 49 N. A non-heat-fusible polymer means a polymer that does not have a temperature at which the melt flow rate is 1 to 1000 g / 10 min under a load of 49 N. From the viewpoint of heat resistance, the melting temperature of the F polymer is preferably 200° C. or higher, more preferably 260° C. or higher. From the viewpoint of ease of processing, the melting temperature of the F polymer is preferably 325° C. or lower, more preferably 320° C. or lower.

[0019] From the viewpoint of heat resistance, the glass transition point of the F polymer is preferably 50° C. or higher, and more preferably 75° C. or higher. From the viewpoint of ease of processing, the glass transition point of the F polymer is preferably 150° C. or lower, and more preferably 125° C. or lower. The fluorine content of the F polymer is preferably 70% by mass or more, more preferably 72 to 76% by mass, from the viewpoint of favorable expression of properties due to fluorine atoms, such as electrical properties and heat resistance. The surface tension of the F polymer is preferably 16 to 26 mN / m. The surface tension of the F polymer can be measured by placing a droplet of a wettability index reagent (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) on a flat plate made of the F polymer.

[0020] F polymer is preferably polytetrafluoroethylene (PTFE), a polymer containing TFE units and units based on ethylene, a polymer containing TFE units and units based on propylene, a polymer containing TFE units and units based on perfluoro(alkyl vinyl ether) (PAVE) (PAVE units) (PFA), and a polymer containing TFE units and units based on hexafluoropropylene (FEP), more preferably a polymer containing TFE units and at least one of PAVE units and units based on hexafluoropropylene, and more preferably PFA and FEP from the viewpoint of properties such as thermal conductivity, adhesiveness, and processability.These polymers may further contain units based on other comonomers. PAVE is preferably CF2=CFOCF3, CF2=CFOCF2CF3 or CF2=CFOCF2CF2CF3 (hereinafter also referred to as "PPVE"), and more preferably PPVE.

[0021] In particular, from the viewpoint of obtaining a non-aqueous dispersion with high uniformity and improving the adhesion of the molded article obtained therefrom, the F polymer preferably has an oxygen-containing polar group, more preferably has a hydroxyl group-containing group or a carbonyl group-containing group, and even more preferably has a carbonyl group-containing group.

[0022] The hydroxy group-containing group is preferably a group containing an alcoholic hydroxy group, and more preferably -CF2CH2OH or -C(CF3)2OH. The carbonyl group-containing group is preferably a carboxyl group, an alkoxycarbonyl group, an amide group, an isocyanate group, a carbamate group (-OC(O)NH2), an acid anhydride residue (-C(O)OC(O)-), an imide residue (-C(O)NHC(O)-, etc.) or a carbonate group (-OC(O)O-), and more preferably an acid anhydride residue.

[0023] When the F polymer has a carbonyl group-containing group, the number of carbonyl group-containing groups in the F polymer is 1×10 6 The number of carbonyl-containing groups per unit is preferably 10 to 5000, more preferably 100 to 3000. The number of carbonyl-containing groups in the F polymer can be quantified by the composition of the polymer or the method described in WO 2020 / 145133. The carbonyl group-containing group may be contained in a unit based on a monomer in the F polymer, or may be contained in a terminal group of the main chain of the F polymer, the former being preferred. Examples of the latter include an F polymer having a carbonyl group-containing group as a terminal group derived from a polymerization initiator, a chain transfer agent, etc., and an F polymer obtained by subjecting an F polymer to plasma treatment or ionizing radiation treatment.

[0024] The monomer having a carbonyl group-containing group is preferably itaconic anhydride, citraconic anhydride, or 5-norbornene-2,3-dicarboxylic anhydride (hereinafter also referred to as "NAH"), and more preferably NAH.

[0025] The F polymer is a poly(ethylene glycol) copolymer having a carbonyl-containing group, which includes a TFE unit and a PAVE unit. It is preferably a polymer containing a TFE unit, a PAVE unit, and a unit based on a monomer having a carbonyl group-containing group, and more preferably a polymer containing these units in this order in an amount of 90 to 99 mol%, 0.99 to 9.97 mol%, and 0.01 to 3 mol% relative to the total units. Specific examples of such F polymers include the polymers described in WO 2018 / 016644.

[0026] The F particles are particles containing an F polymer, preferably consisting of an F polymer as the main component, and preferably consisting of an F polymer. The fact that the F polymer is the main component means that the content of the F polymer is relatively high compared to the content of each of the other components on a volume basis.

[0027] From the viewpoint of dispersion stability, the D50 of the F particles is preferably 0.1 μm or more, more preferably more than 0.3 μm, and even more preferably 1 μm or more. From the viewpoint of dispersion stability, the D50 of the F particles is preferably 25 μm or less, more preferably 10 μm or less, even more preferably 8 μm or less, and particularly preferably 5 μm or less. The specific surface area of ​​F particles is 1 to 25 m 2 / g is preferred.

[0028] F particles may be used alone or in combination of two or more. When two or more types of F particles are used in combination, different F particles refer to F particles that differ in average particle size, type of F polymer, content of F polymer, presence or absence of other components other than F polymer, content of other components, or combinations thereof.

[0029] The content of F particles in the non-aqueous dispersion is preferably 30% by mass or more, more preferably 40% by mass or more. The content of F particles in the non-aqueous dispersion is preferably 70% by mass or less, more preferably 60% by mass or less. When the content of F particles in the non-aqueous dispersion is within the above range, sedimentation of the F particles in the non-aqueous dispersion is easily suppressed, and the viscosity retention rate during storage is more excellent.

[0030] (Modified Cellulose) Modified cellulose is cellulose having hydroxyalkyloxy groups, in which at least a portion of the hydroxy groups of cellulose are modified with hydroxyalkyl groups to form hydroxyalkyloxy moieties. The number of alkyloxy groups in the hydroxyalkyloxy moiety may be one (one unit, mono) or two or more (two or more units, poly), with 1 to 10 being preferred. The number of carbon atoms in the alkyl in the hydroxyalkyloxy moiety is preferably 1 to 4, and more preferably 2. In the case of polyalkyloxy, the number of carbon atoms in the alkyl refers to the number of carbon atoms per unit.

[0031] In the modified cellulose, the content of the hydroxyalkyl moiety, which is a partial structure of the hydroxyalkyloxy group, is preferably 50% by mass or more. The content of the hydroxyalkyl moiety is preferably 80% by mass or less. When the content of the hydroxyalkyl moiety is within this range, the modified cellulose more effectively balances the affinity with the solvent and the F particles, which makes it easier to suppress the sedimentation of the F particles in the non-aqueous dispersion, and provides a better viscosity retention rate during storage. It should be noted that a hydroxyalkyl group directly bonded to a six-membered ring does not have an oxy group, and therefore such a hydroxyalkyl group is not included in the above content.

[0032] The average degree of substitution A with hydroxyalkyloxy groups per glucose unit is preferably 0.05 or more, more preferably 0.1 or more. The average degree of substitution A is preferably 0.4 or less, more preferably 0.3 or less. When the average degree of substitution A is within this range, the modified cellulose more effectively balances the affinity with the solvent and the F particles, which makes it easier to suppress the sedimentation of the F particles in the non-aqueous dispersion, and provides a better viscosity retention rate during storage.

[0033] Modified cellulose can be obtained, for example, by reacting raw cellulose with sodium hydroxide to obtain alkali cellulose, and then subjecting the alkali cellulose to a substitution reaction with an alkylene oxide, which substitutes some or all of the hydroxyl groups in the glucose ring units of the cellulose.

[0034] The modified cellulose may have at least a portion of its hydroxyl groups modified with an alkyl group. The hydroxyl groups to be protected may be hydroxyl groups contained in a hydroxyalkyloxy group, or hydroxyl groups that the cellulose originally has and are not protected with a hydroxyalkyl group, or both.

[0035] The modification rate with alkyl groups (hereinafter also referred to as "average substitution degree B") is preferably 1.0 or more, more preferably 1.3 or more, per glucose unit. The average substitution degree of alkyl groups is preferably 2.0 or less, more preferably 1.6 or less. When the average substitution degree B is within the above range, the modified cellulose more effectively balances the affinity with the solvent and the F particles, which makes it easier to suppress the sedimentation of the F particles in a non-aqueous dispersion, and provides better viscosity retention during storage.

[0036] Here, the degree of substitution by the alkyl group in the modified cellulose is defined as the degree of substitution C. The degree of substitution C is the total value of the degrees of substitution of alkyl groups in the following cases: (I) when the hydroxyl groups in a glucose unit are substituted only with alkyl groups; (II) when the glucose unit contains both sites substituted with alkyl groups and hydroxyalkyloxy groups; and (III) when the hydroxyl group of the hydroxyalkyloxy group in a glucose unit is further substituted with an alkyl group.

[0037] Furthermore, in glucose units that do not have a hydroxyalkyloxy group (i.e., glucose units in which all hydroxy groups are not protected with hydroxyalkyl groups) among the glucose units that constitute the modified cellulose, the degree of substitution of the alkyl group directly substituted on the hydroxy group on the 6-position carbon is defined as the substitution degree D. The degree of substitution D is the total value when at least the alkyl group at the 6th position is substituted among the three hydroxyl groups at the 2nd, 3rd and 6th positions of the glucose unit that can be substituted. Therefore, the hydroxyl groups at the 2nd and 3rd positions may or may not be substituted.

[0038] The ratio of the degree of substitution D to the degree of substitution C (degree of substitution D / degree of substitution C) is preferably 0.30 or more. The ratio (degree of substitution D / degree of substitution C) is preferably 0.37 or less, more preferably 0.35 or less. When the ratio (degree of substitution D / degree of substitution C) is within the above range, the modified cellulose more effectively balances the affinity with the solvent and the F particles, which makes it easier to suppress the sedimentation of the F particles in the non-aqueous dispersion, and provides a more excellent viscosity retention rate during storage.

[0039] Modified cellulose in which at least a portion of the hydroxyl groups are protected with alkyl groups can be obtained by reacting raw cellulose with sodium hydroxide to obtain alkali cellulose, and then reacting the alkali cellulose with an alkyl etherifying agent such as methyl chloride and a hydroxyalkyl etherifying agent such as alkylene oxide.

[0040] The weight-average degree of polymerization of the modified cellulose is preferably at least 10, more preferably at least 80, and even more preferably at least 350. Moreover, the weight-average degree of polymerization of the modified cellulose is preferably not more than 5000, more preferably not more than 4000, and even more preferably not more than 2000. When the weight-average degree of polymerization of the modified cellulose is within the above range, sedimentation of the F particles in the non-aqueous dispersion is more easily suppressed, and the viscosity retention rate during storage is more excellent. The weight-average degree of polymerization of the modified cellulose can be determined by measuring the weight-average molecular weight by a combination of gel permeation chromatography and light scattering according to the molecular weight measurement method described in Polymer Research, Vol. 39, No. 4, pp. 293-298 (1982), and dividing the weight-average molecular weight by the molecular weight per unit hydroxypropylmethylcellulose molecule.

[0041] The content of the modified cellulose relative to the content of the F particles is preferably 3.0% by mass or less, more preferably 2.5% by mass or less, and even more preferably 2.0% by mass or less. When the content of the modified cellulose is within the above range, the physical properties of the molded article formed from the dispersion are likely to be improved. The content of the modified cellulose relative to the content of the F particles is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and even more preferably 1% by mass or more. When the content of the modified cellulose is within the above range, the effect of adding the modified cellulose is more effectively exhibited.

[0042] The content of the modified cellulose in the total amount of the nonaqueous dispersion is preferably 5% by mass or less, more preferably 2% by mass or less, and even more preferably 1% by mass or less. When the content of the modified cellulose is within the above range, the physical properties of the molded article formed from the dispersion are likely to be improved. The content of the modified cellulose in the total amount of the non-aqueous dispersion is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and even more preferably 1% by mass or more. When the content of the modified cellulose is within the above range, the effect of adding the modified cellulose is more effectively exhibited.

[0043] (Non-aqueous dispersion medium) The non-aqueous dispersion medium is a compound that is liquid at 25° C. under atmospheric pressure, and preferably has a boiling point of 50 to 240° C. One type of non-aqueous dispersion medium may be used, or two or more types may be used. When two types of non-aqueous dispersion media are used, the two types of non-aqueous dispersion media are preferably compatible with each other. The non-aqueous dispersion medium is preferably a compound selected from the group consisting of amides, ketones and esters. Amides include N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, N,N-dimethylpropanamide, 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide, N,N-diethylformamide, hexamethylphosphoric triamide, and 1,3-dimethyl-2-imidazolidinone. Ketones include acetone, methyl ethyl ketone, methyl isopropyl ketone, methyl isobutyl ketone, methyl n-pentyl ketone, methyl isopentyl ketone, 2-heptanone, cyclopentanone, cyclohexanone, and cycloheptanone. Esters include methyl acetate, ethyl acetate, butyl acetate, methyl lactate, ethyl lactate, methyl pyruvate, ethyl pyruvate, methyl methoxypropionate, ethyl ethoxypropionate, ethyl 3-ethoxypropionate, gamma-butyrolactone, and gamma-valerolactone.

[0044] The content of the non-aqueous dispersion medium can be appropriately adjusted in consideration of the coating method, the thickness of the molded product to be produced, etc., and is, for example, preferably 40% by volume or more, more preferably 60% by volume or more, based on the total volume of the non-aqueous dispersion liquid. The content of the non-aqueous dispersion medium is preferably 90% by volume or less, more preferably 80% by volume or less, based on the total volume of the non-aqueous dispersion liquid. The solid content in the non-aqueous dispersion is preferably 10% by volume or more, more preferably 20% by volume or more, based on the total volume of the non-aqueous dispersion. The solid content concentration is preferably 80% by volume or less. The solid content means the total amount of substances that form the solid content in the molded product formed from the non-aqueous dispersion. Specifically, the F particles and modified cellulose are included in the solid content, and when the non-aqueous dispersion contains other resins, the other resins are also included in the solid content.

[0045] (Other ingredients) The non-aqueous dispersion may contain particles of fluororesin other than F polymer (hereinafter also referred to as "other F particles"). Examples of the other fluororesin include melt processable fluororesin other than F polymer and non-melt processable fluororesin other than F polymer, and from the viewpoint of moldability, melt processable fluororesin other than F polymer is preferred. The melt processable fluororesin other than F polymer is a melt processable fluororesin that does not contain a TFE unit. When F particles are used in combination with other F particles, the proportion of the other F particles in the total amount of the F particles and the other F particles is preferably less than 50% by mass, more preferably 25% by mass or less, and is preferably 0.1% by mass or more, more preferably 1% by mass or more.

[0046] The non-aqueous dispersion may contain a resin other than the fluororesin. The other resin may be contained in the non-aqueous dispersion as powder particles, or may be dissolved or dispersed in the non-aqueous dispersion medium. Examples of the other resin include polyester resins such as liquid crystalline aromatic polyesters, imide resins, epoxy resins, maleimide resins, urethane resins, polyphenylene ether resins, polyphenylene oxide resins, and polyphenylene sulfide resins. The other resins are preferably aromatic polymers, and more preferably at least one aromatic imide polymer selected from the group consisting of aromatic polyimides, aromatic polyamic acids, aromatic polyamideimides, and aromatic polyamideimide precursors. The aromatic polymer is preferably contained in the non-aqueous dispersion as a varnish dissolved in the non-aqueous dispersion medium. Specific examples of aromatic imide polymers include the "UPIA-AT" series (manufactured by Ube Industries, Ltd.), the "NEOPLUMI (registered trademark)" series (manufactured by Mitsubishi Gas Chemical Company, Inc.), the "SPIXELIA (registered trademark)" series (manufactured by Somar), the "Q-PILON (registered trademark)" series (manufactured by PI Technical Research Institute, Ltd.), the "WINGO" series (manufactured by Wingo Technology Co., Ltd.), the "TOMAID (registered trademark)" series (manufactured by T&K TOKA Corporation), the "KPI-MX" series (manufactured by Kawamura Sangyo Co., Ltd.), and "HPC-1000" and "HPC-2100D" (both manufactured by Showa Denko Materials Co., Ltd.).

[0047] When the non-aqueous dispersion contains other resins, the content of the other resins relative to the F particles is preferably 0.1% by volume or more, more preferably 1% by volume or more, and is preferably 15% by volume or less, more preferably 10% by volume or less.

[0048] From the viewpoint of further improving the dispersion stability, the non-aqueous dispersion may contain a surfactant. The surfactant is preferably a nonionic surfactant, and specific examples of the nonionic surfactant include the "Ftergent" series (manufactured by Neos), the "Surflon" (registered trademark) series (manufactured by AGC Seimi Chemical Co., Ltd.), the "Megafac" (registered trademark) series (manufactured by DIC Corporation), the "Unidyne" series (manufactured by Daikin Industries, Ltd.), "BYK-347", "BYK-349", "BYK-378", "BYK-3450", "BYK-3451", "BYK-3455", "BYK-3456" (manufactured by BYK Japan), "KF-6011", "KF-6043" (manufactured by Shin-Etsu Chemical Co., Ltd.), and the "Tergitol" series (manufactured by The Dow Chemical Company, "Tergitol TMN-100X", etc.). When the non-aqueous dispersion of the present disclosure contains a surfactant, the content of the surfactant in the non-aqueous dispersion is preferably 1 to 15% by volume.

[0049] The aqueous dispersion may further contain an inorganic filler, in which case the molded product produced from the aqueous dispersion tends to have excellent electrical properties and low linear expansion. The inorganic filler is preferably a nitride filler or an inorganic oxide filler, more preferably a boron nitride filler, a beryllia filler (a beryllium oxide filler), a silicate filler (a silica filler, a wollastonite filler, a talc filler), or a metal oxide (such as cerium oxide, aluminum oxide, magnesium oxide, zinc oxide, or titanium oxide) filler, and even more preferably a silica filler.

[0050] It is preferable that at least a portion of the surface of the inorganic filler is surface-treated with a silane coupling agent (3-aminopropyltriethoxysilane, vinyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-isocyanatopropyltriethoxysilane, etc.).

[0051] The inorganic filler preferably has a D50 of 20 μm or less, more preferably 10 μm or less, and more preferably has a D50 of 0.01 μm or more, more preferably 0.1 μm or more. The shape of the inorganic filler may be any of granular, needle-like (fibrous) and plate-like. Specific shapes of the inorganic filler include spherical, scale-like, layered, leaf-like, apricot kernel-like, columnar, cockscomb-like, equiaxial, leaf-like, micaceous, block-like, flat, wedge-like, rosette-like, net-like and prismatic shapes.

[0052] The inorganic filler may be used alone or in combination of two or more kinds. When the aqueous dispersion further contains an inorganic filler, the amount thereof is preferably 1 to 50 mass %, more preferably 5 to 40 mass %, based on the total mass of the aqueous dispersion.

[0053] Specific examples of suitable inorganic fillers include silica fillers (such as the "Admafine (registered trademark)" series manufactured by Admatechs Co., Ltd.), zinc oxide surface-treated with an ester such as propylene glycol dicaprylate (such as the "FINEX (registered trademark)" series manufactured by Sakai Chemical Industry Co., Ltd.), spherical fused silica fillers (such as the "SFP (registered trademark)" series manufactured by Denka Co., Ltd.), titanium oxide fillers coated with polyhydric alcohol and inorganic substances (such as the "Tipaque (registered trademark)" series manufactured by Ishihara Sangyo Kaisha, Ltd.), and rutile-type titanium oxide fillers surface-treated with alkylsilanes (such as the "Tepaque (registered trademark)" series manufactured by Ishihara Sangyo Kaisha, Ltd.). Examples of fillers include the "JMT (registered trademark)" series manufactured by Ika Corporation), hollow silica fillers (the "E-SPHERES" series manufactured by Taiheiyo Cement Corporation, the "Silinax" series manufactured by Nippon Steel Mining Co., Ltd., the "Ecocospher" series manufactured by Emerson & Cumming Co., Ltd., etc.), talc fillers (the "SG" series manufactured by Nippon Talc Co., Ltd., etc.), steatite fillers (the "BST" series manufactured by Nippon Talc Co., Ltd., etc.), and boron nitride fillers (the "UHP" series manufactured by Showa Denko KK, the "Denka Boron Nitride" series ("GP" and "HGP" grades) manufactured by Denka Co., Ltd., etc.).

[0054] The non-aqueous dispersion may further contain a silane coupling agent from the viewpoint of further improving the miscibility between the F polymer and the inorganic filler. Examples of the silane coupling agent include the same silane coupling agents as those that may be used in the surface treatment of the inorganic filler, and the preferred ranges thereof are also the same. When the non-aqueous dispersion contains a silane coupling agent, the content of the silane coupling agent in the non-aqueous dispersion (excluding that used for surface treatment of the inorganic filler) is preferably 1 to 10% by volume relative to the total volume of the non-aqueous dispersion.

[0055] The non-aqueous dispersion may further contain additives such as a thixotropic agent, a viscosity modifier, an antifoaming agent, a dehydrating agent, a plasticizer, a weathering agent, an antioxidant, a heat stabilizer, a lubricant, an antistatic agent, a whitening agent, a colorant, a conductive material, a release agent, a surface treatment agent, a flame retardant, and a conductive filler.

[0056] (moisture content) The water content of the non-aqueous dispersion is 10,000 ppm by mass or less, preferably 1,000 ppm by mass or less, and preferably 1 ppm by mass or more.

[0057] (Physical properties of non-aqueous dispersion) The viscosity of the non-aqueous dispersion at 25°C is preferably 50 mPa·s or more, more preferably 100 mPa·s or more, and even more preferably 500 mPa·s or more. When the viscosity is within the above range, the non-aqueous dispersion is appropriately thickened, and the settling of the F particles is more easily suppressed. The viscosity of the non-aqueous dispersion at 25°C is preferably 10,000 mPa·s or less, and more preferably 3,000 mPa·s or less.

[0058] When the non-aqueous dispersion is stored in a container at 25°C for one month, the rate of change in viscosity before and after storage, represented by the following formula (hereinafter also referred to as "viscosity retention rate"), is preferably 75% or more, more preferably 80% or more, even more preferably 85% or more, and particularly preferably 90% or more. Viscosity retention rate = Viscosity after storage (mPa s) / Viscosity before storage (mPa s) × 100

[0059] The thixotropy ratio of the non-aqueous dispersion is preferably equal to or less than 6, more preferably equal to or less than 5, and even more preferably equal to or less than 4. The thixotropy ratio of the non-aqueous dispersion is preferably equal to or more than 1, and more preferably equal to or more than 2. When the thixotropy ratio of the non-aqueous dispersion is within the above range, sedimentation of the F particles is further suppressed, and the viscosity retention rate after storage is more excellent.

[0060] <Method for producing non-aqueous dispersion> The non-aqueous dispersion of the present disclosure can be obtained by mixing F particles and modified cellulose, and, if necessary, additives such as other resins, non-aqueous dispersion media, surfactants, silane coupling agents, etc. The order of mixing is not particularly limited, and the mixing method may be either mixing all at once or mixing in multiple batches.

[0061] Examples of mixing devices for obtaining the nonaqueous dispersion of the present disclosure include stirring devices equipped with blades, such as a Henschel mixer, a pressure kneader, a Banbury mixer, and a planetary mixer; grinding devices equipped with media, such as a ball mill, an attritor, a basket mill, a sand mill, a sand grinder, a Dyno Mill, a Dispermat, an SC Mill, a spike mill, and an agitator mill; and dispersing devices equipped with other mechanisms, such as a microfluidizer, a nanomizer, an ultimizer, an ultrasonic homogenizer, a dissolver, a disperser, a high-speed impeller, a thin film swirling high-speed mixer, a planetary stirrer, and a V-type mixer.

[0062] <Applications of non-aqueous dispersions> The use of the non-aqueous dispersion of the present disclosure is not particularly limited, and can be used, for example, for the production of molded products. In particular, the non-aqueous dispersion of the present disclosure is suitable for applications in which it is desired to favorably express the properties of the F polymer contained in the non-aqueous dispersion.

[0063] The non-aqueous dispersion is useful as a material for imparting insulating properties, heat resistance, corrosion resistance, chemical resistance, water resistance, impact resistance, thermal conductivity, and the like. Specifically, the nonaqueous dispersion can be used in printed wiring boards, thermal interface materials, substrates for power modules, coils used in power devices such as motors, in-vehicle engines, heat exchangers, vials, syringes, ampoules, medical wires, secondary batteries such as lithium ion batteries, primary batteries such as lithium batteries, radical batteries, solar cells, fuel cells, lithium ion capacitors, hybrid capacitors, capacitors (aluminum electrolytic capacitors, tantalum electrolytic capacitors, etc.), electrochromic elements, electrochemical switching elements, electrode binders, electrode separators, electrodes (positive electrodes, negative electrodes), and the like. The non-aqueous dispersion is also useful as an adhesive for bonding parts. Specifically, the non-aqueous dispersion can be used for bonding ceramic parts, metal parts, electronic parts such as IC chips, resistors, and capacitors on substrates of semiconductor elements and module parts, bonding circuit boards and heat sinks, bonding LED chips to substrates, etc.

[0064] <Method of manufacturing laminate> The method for producing the laminate of the present disclosure involves applying the non-aqueous dispersion of the present disclosure to a substrate, heating to remove the non-aqueous dispersion medium, and further heating to melt and sinter the F particles.

[0065] Examples of the substrate include metal substrates (metal foils of copper, nickel, aluminum, titanium, alloys thereof, etc.), heat-resistant resin films (heat-resistant resin films of polyimide, polyamide, polyetheramide, polyphenylene sulfide, polyaryl ether ketone, polyamideimide, liquid crystalline polyester, tetrafluoroethylene polymer, etc.), prepreg substrates (precursors of fiber-reinforced resin substrates), ceramic substrates (ceramic substrates such as silicon carbide, aluminum nitride, silicon nitride, etc.), and glass substrates.

[0066] The shape of the substrate may be flat, curved or uneven, and may be any of foil, plate, film and fiber (woven fabric, nonwoven fabric, etc.). The ten-point average roughness of the surface of the substrate is preferably 0.01 to 0.05 μm. The surface of the substrate may be surface-treated with a silane coupling agent or plasma-treated. Examples of such silane coupling agents include the same silane coupling agents as those that may be used for surface treatment of inorganic fillers. The peel strength between the fluororesin layer and the substrate is preferably 10 N / cm or more, more preferably 15 N / cm or more, and is preferably 100 N / cm or less.

[0067] Methods for applying the non-aqueous dispersion include a coating method, a droplet discharging method, and a dipping method, and preferably a roll coating method, a knife coating method, a bar coating method, a die coating method, or a spray method. The heating for removing the non-aqueous dispersion medium is preferably performed at 100 to 200°C for 0.1 to 30 minutes. In this heating, the non-aqueous dispersion medium does not need to be completely removed, but only needs to be removed to an extent that the layer formed by packing of the F particles and the composite particles can maintain a self-supporting film. In addition, when heating, air may be blown to promote the removal of the non-aqueous dispersion medium by air drying. The heating for calcining the F polymer is preferably carried out at a temperature equal to or higher than the calcination temperature of the F polymer, more preferably at 360 to 400° C. for 0.1 to 30 minutes. The heating device for each heating may be an oven or a ventilation drying furnace. The heat source in the device may be a contact type heat source (hot air, hot plate, etc.) or a non-contact type heat source (infrared rays, etc.). The heating may be carried out under normal pressure or under reduced pressure. The atmosphere during each heating may be either an air atmosphere or an inert gas atmosphere (helium gas, neon gas, argon gas, nitrogen gas, etc.).

[0068] The fluororesin layer is formed through the steps of applying a non-aqueous dispersion and heating. These steps may be performed once each, or may be repeated two or more times. For example, a non-aqueous dispersion may be applied to the surface of a substrate and heated to form a fluororesin layer, and a non-aqueous dispersion may be applied to the surface of the fluororesin layer and heated to form a second fluororesin layer. In addition, at the stage where a non-aqueous dispersion is applied to the surface of a substrate and heated to remove the non-aqueous dispersion medium, a non-aqueous dispersion may be applied to the surface and heated to form a fluororesin layer. The non-aqueous dispersion may be applied to only one surface of the substrate, or may be applied to both surfaces of the substrate. In the former case, a laminate having a substrate layer and a fluororesin layer on one surface of the substrate layer is obtained, and in the latter case, a laminate having a substrate layer and a fluororesin layer on both surfaces of the substrate layer is obtained.

[0069] The thickness of the fluororesin layer can be appropriately selected depending on the application, and may be, for example, 25 μm or more, 30 μm or more, or 40 μm or more, or may be 200 μm or less.

[0070] Suitable specific examples of the laminate include a metal-clad laminate having a metal foil and a fluororesin layer on at least one surface of the metal foil, and a multilayer film having a polyimide film and a fluororesin layer on both surfaces of the polyimide film.

[0071] Laminates formed from non-aqueous dispersions are useful as antenna parts, printed circuit boards, aircraft parts, automobile parts, sporting goods, food industry products, heat dissipation parts, and the like. Specifically, these include electric wire coating materials (aircraft electric wires, etc.), enameled wire coating materials used in motors for electric vehicles, etc., electrical insulating tape, insulating tape for oil drilling, oil transport hoses, hydrogen tanks, materials for printed circuit boards, separation membranes (microfiltration membranes, ultrafiltration membranes, reverse osmosis membranes, ion exchange membranes, dialysis membranes, gas separation membranes, etc.), electrode binders (for lithium secondary batteries, for fuel cells, etc.), copy rolls, furniture, automobile dashboards, covers for home appliances, etc., sliding parts (load bearings, yaw bearings, sliding shafts, valves, bearings, bushings, seals, thrust washers, wear rings, etc.), and other applications. They are useful as: tools, pistons, slide switches, gears, cams, conveyor belts, food transport belts, etc.), tension ropes, wear pads, wear strips, tube lamps, test sockets, wafer guides, wear parts of centrifugal pumps, chemical and water supply pumps, tools (shovels, files, hacksaws, etc.), boilers, hoppers, pipes, ovens, baking molds, chutes, racket strings, dies, toilets, container coating materials, heat dissipation boards mounted for power devices, heat dissipation members for wireless communication devices, transistors, thyristors, rectifiers, transformers, power MOS FETs, CPUs, heat dissipation fins, metal heat sinks, blades for windmills, wind power generation equipment, aircraft, etc., housings for personal computers and displays, electronic device materials, interior and exterior parts of automobiles, sealing materials for processing machines and vacuum ovens that perform heat treatment under low oxygen conditions, plasma processing equipment, heat dissipation parts in processing units for sputtering and various dry etching equipment, electromagnetic wave shielding, etc.

[0072] Laminates formed from the nonaqueous dispersion of the present disclosure are useful as electronic substrate materials such as flexible printed wiring boards and rigid printed wiring boards, protective films and heat dissipation substrates, particularly heat dissipation substrates for automobiles. EXAMPLES

[0073] Next, the embodiments of the present disclosure will be specifically described using examples, but the embodiments of the present disclosure are not limited to these examples.

[0074] [Example 1] (Preparation of F particles) The F particles contain 97.9 mol% of TFE units, 0.1 mol% of NAH units, and 2.0 mol% of PPVE units, in that order, and have a carbonyl group-containing group with a main chain carbon number of 1×10 6 Particles (D50: 2.1 μm) of a tetrafluoroethylene polymer (melting temperature: 300° C.) having 1000 particles per particle were prepared.

[0075] (Preparation of modified cellulose 1) Alkali cellulose was treated with methyl chloride and propylene oxide was added to obtain modified cellulose 1 having hydroxypropyloxy groups and in which at least a portion of the hydroxy groups had been modified with methyl.

[0076] (Preparation of non-aqueous dispersion) F particles, the modified cellulose 1 obtained above, and N-methyl-2-pyrrolidone were mixed and subjected to shear stirring to prepare dispersion 1. Dispersion 1 contained 40 mass% F particles and 1 mass% modified cellulose 1. Dispersion 1 had a viscosity of 1000 mPa s and a thixotropic ratio of 3.0.

[0077] [Example 2] Dispersion 2 was prepared in the same manner as in Example 1, except that modified cellulose 1 was replaced with hydroxypropyl cellulose (Celny M, manufactured by Nippon Soda Co., Ltd., having a hydroxypropyloxy group).

[0078] [Example 3] Dispersion 3 was prepared in the same manner as in Example 1, except that methoxyethyl cellulose was used instead of modified cellulose 1.

[0079] [Example 4] Dispersion 4 was prepared in the same manner as in Example 1, except that water was added so that the water content was the amount shown in Table 1.

[0080] <Evaluation> The following evaluations were carried out for each dispersion, and the results are summarized in Table 1 below. (sedimentation) The resulting dispersion was stored in a container at 25°C for one month, and the sedimentation properties were checked. The evaluation criteria were as follows: A: No sedimentation or redispersion possible by shaking hands B: Redispersion is possible when stirred with a bead mill C: Cannot be redispersed even when stirred with a bead mill

[0081] (viscosity) The viscosity was measured before and after storing in a container at 25°C for one month.

[0082] [Table 1]

Claims

1. A non-aqueous dispersion containing particles including a tetrafluoroethylene-based polymer, a non-aqueous dispersion medium, and cellulose having a hydroxyalkyloxy group, the non-aqueous dispersion having a water content of 10,000 ppm by mass or less.

2. The non-aqueous dispersion according to claim 1, having a viscosity at 25°C of 50 mPa·s or more.

3. 3. The non-aqueous dispersion according to claim 1, wherein the tetrafluoroethylene-based polymer comprises units based on tetrafluoroethylene and at least one of units based on perfluoro(alkyl vinyl ether) and units based on hexafluoropropylene.

4. The non-aqueous dispersion according to claim 1 or 2, wherein the tetrafluoroethylene-based polymer has a carbonyl group-containing group.

5. The tetrafluoroethylene polymer has a main chain carbon number of 1×10 6 The non-aqueous dispersion according to claim 4, wherein each of the particles has 10 to 5,000 carbonyl-containing groups.

6. 3. The nonaqueous dispersion according to claim 1, wherein the content of the particles containing the tetrafluoroethylene-based polymer is 30 to 70 mass %.

7. The non-aqueous dispersion according to claim 1 or 2, wherein the non-aqueous dispersion medium contains at least one selected from the group consisting of amides, ketones, and esters.

8. The non-aqueous dispersion according to claim 1 or 2, wherein at least a portion of hydroxyl groups of the cellulose are modified with alkyl groups.

9. 3. The nonaqueous dispersion according to claim 1, wherein the cellulose contains 50 to 80 mass % of hydroxyalkyl moieties, which are partial structures of the hydroxyalkyloxy groups.

10. The nonaqueous dispersion according to claim 1 or 2, wherein a content of the cellulose relative to a content of the particles containing the tetrafluoroethylene-based polymer is 3 mass % or less.

11. The non-aqueous dispersion according to claim 1 , wherein the content of the cellulose in the total amount of the non-aqueous dispersion is 2 mass % or less.

12. The nonaqueous dispersion according to claim 1 or 2, which has a water content of 1000 ppm by mass or less.

13. Viscosity η measured at a rotation speed of 30 rpm 1 The viscosity η measured at a rotation speed of 60 rpm 2 The nonaqueous dispersion according to claim 1 or 2, wherein a thixotropy ratio calculated by dividing by 1 / 2 is 6 or less.

14. The non-aqueous dispersion according to claim 1 or 2, further comprising a surfactant.

15. A method for producing a laminate, comprising applying the nonaqueous dispersion according to claim 1 or 2 to a substrate, heating to remove the nonaqueous dispersion medium, and further heating to melt and sinter the particles containing the tetrafluoroethylene-based polymer.

Citation Information

Patent Citations

  • Fluororesin particle nonaqueous dispersion

    JP2021181537A